Enhancing peer-learning and feedback-learning through self-regulated learning in online mathematics for undergraduates’ academic achievement and satisfaction - Abdulrahman, Ahmed Alhassan; Said Husain, Sharifah Kartini; Letchumanan, Malathi; Yunos, Faridah (Common Ground Research Networks, 2025)
This study employed quantitative research to determine the impact of three interventions (self-regulated learning [SRL], peer-support learning [PSL], and feedback-support learning [FSL]) on learning achievement and satisfaction in resolving the problems students face when learning online mathematics. Generally, learning strategies and skills are critical to the success of all learners of mathematics. Many undergraduate students are not ready to study courses related to mathematics; lack of learning strategies associated with previous failure in online mathematics assessment is the number one factor undermining student achievement. This study adopted a true experimental research design. The study aims to determine the impact of these three learning group strategies—SRL, SRL with PSL, SRL with FSL—on online mathematics achievement and satisfaction. Our one-way ANOVA analysis showed that students who used SRL/PSL were better in terms of academic achievement and online-learning satisfaction.